Lecznictwo w krajach Unii Europejskiej. Czego mogą spodziewać się przyszli członkowie UE? - Grewe, Rolf (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The problems of national health system in the European Community member states and affiliating countries will be discussed. Particular attention will be paid to team doctor model, continuous medical education, social security system and disease management programme.